2013
DOI: 10.1016/j.ajo.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Systemic Cytokines and Complement Factor H Y402H Polymorphism in Patients With Dry Age-Related Macular Degeneration

Abstract: The elevated systemic levels of selected proinflammatory cytokines, including those representing products of inflammasome activation, were associated with the CC at-risk variant of the Y402H polymorphism and suggest that genetic factors regulate the inflammatory status in dry AMD patients. Our data support the central role of inflammation in the pathogenesis of AMD and provide further evidence of a systemic involvement in AMD etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 44 publications
4
54
0
2
Order By: Relevance
“…These findings in outer retina support and extend our earlier finding of an association between systemic (plasma) levels of cytokines and the at-risk variant in the CFH gene and highlight the idea that individuals with the at-risk variant of CFH gene may have a high proinflammatory status in the outer retina 4. Presently, we do not know whether C5a, TNF-α or IL-18 is derived from the blood circulation or from the retinal microenvironment including RPE, or both.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These findings in outer retina support and extend our earlier finding of an association between systemic (plasma) levels of cytokines and the at-risk variant in the CFH gene and highlight the idea that individuals with the at-risk variant of CFH gene may have a high proinflammatory status in the outer retina 4. Presently, we do not know whether C5a, TNF-α or IL-18 is derived from the blood circulation or from the retinal microenvironment including RPE, or both.…”
Section: Discussionsupporting
confidence: 88%
“…Our earlier study, and those of others, reported that the at-risk variant is associated with the elevated levels of complement activation products and classic proinflammatory cytokines systemically, in the blood of patients with AMD 4 5. The extent to which systemic levels of cytokines and complement proteins may affect the local retinal tissues is important to understand the AMD pathologies, particularly in light of a recent finding that there is an increase of membrane attack complex (MAC), the terminal end product of complement pathway in the choroidal tissues from donors with the at-risk variant 6.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Thus, RPE cells are in constant, direct contact with these bioactive substances that, therefore, represent candidates for the inflammasome priming signal in AMD via anaphylatoxin receptors such as C5aR that is expressed on the basolateral side of the RPE (28). Indeed, AMD patients with the CFH risk genotype exhibit significantly increased systemic levels of the inflammasome-regulated cytokine IL-18 as compared with AMD patients without the CFH risk genotype, supporting a role for activated complement components in inflammasome activation in AMD (19). In other autoinflammatory diseases such as atherosclerosis and gout, inflammasome priming by complement activation products has likewise been proposed (20,21).…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, a recent study in patients with early or intermediate AMD demonstrated the CFH risk genotype to be associated with significantly increased plasma levels of the inflammasome-regulated cytokine IL-18, suggesting a role for activated complement components like C3a and C5a in inflammasome activation in AMD (19). Inflammasome priming by complement activation products has also been proposed in the context of other diseases such as atherosclerosis and gout (20,21).…”
Section: Age-related Macular Degeneration (Amd)mentioning
confidence: 99%